2013
DOI: 10.1093/nar/gkt282
|View full text |Cite
|
Sign up to set email alerts
|

BLAST: a more efficient report with usability improvements

Abstract: The Basic Local Alignment Search Tool (BLAST) website at the National Center for Biotechnology (NCBI) is an important resource for searching and aligning sequences. A new BLAST report allows faster loading of alignments, adds navigation aids, allows easy downloading of subject sequences and reports and has improved usability. Here, we describe these improvements to the BLAST report, discuss design decisions, describe other improvements to the search page and database documentation and outline plans for future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
746
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,049 publications
(835 citation statements)
references
References 9 publications
4
746
1
10
Order By: Relevance
“…1 C and D and 3A). Furthermore, a protein BLAST search (18), using the SNAP25 interacting regions of Rph3A as a reference, revealed that only DOC2B conserves these contacting residues (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 C and D and 3A). Furthermore, a protein BLAST search (18), using the SNAP25 interacting regions of Rph3A as a reference, revealed that only DOC2B conserves these contacting residues (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
“…The Rph3A C2B residues interacting with the SNAP25 are marked with olive blocks, and that of syt1 C2B with salmon blocks. (B) BLAST alignment (18), using the sequences around the C2B α1-and α2-helices (red rectangles) that form the main interface of the C2B-SNAP25 complex. Blue rectangles show residues interacting with SNAP25, with red stars indicating amino acids that contact the Nt-region II (D51, E52, E55, and R59), and yellow stars highlighting residues that contact Nt-region I (E38, K40, and D41).…”
Section: Methodsmentioning
confidence: 99%
“…Las muestras positivas fueron enviadas a la compañía Macrogen-USA, para ser secuenciadas con los primers 16SrRNAF518 (CCAGCAGCCGCGGTAATACG) y 16SrRNAR800 (TACCAGGGTATCTAATCC). Las secuencias de ARNr 16S fueron reconstruidas utilizando el programa Mega6 (9) y analizadas con BLAST (10) . Basic Local Alignment Search Tool) de NCBI (National Center for Biotechnology Information).…”
Section: Cultivo Microbiológico Estándarunclassified
“…These include sequence similarity [27,28] Among these in-silico methods [52], the basic local alignment search tool (BLAST) [53] revealing protein functions based on excess sequence similarity [54] demonstrated great capacity and attracted substantial interests from the researchers of this field [55,56]. Apart from BLAST, the methods based on the machine learning algorithm (a specific type of artificial intelligence) were frequently used in recent years to predict protein function [57][58][59][60][61][62], and various types of software together with several web-based tools integrating these methods were developed to predict the protein function from sequences irrespective of sequence or structural similarity [36,63].…”
Section: Introductionmentioning
confidence: 99%